Persiapan Deteksi Plat dengan Modifikasi Metode Viola Jones KNN - Purnomo, Jati; Maukar, Maukar (Syntax Idea, 2021)
Currently the system of automatic number plate recognition (ALPR, automatic license plate recognition) has started from anywhere in the country. Letter Plate there is a picture of the license plate number of the vehicle and then an image of the result of the algorithm for shopping alpha numerical images into text format. Although it may seem easy for humans, it turns out that plate detection is very complicated with computers while there are some location-related problems with, point of view, light, and occlusion. The purpose of this study is to know the results of the Can Plate Method Viola Jones KNN. This research methods the Viola Jones method (HaarCasscade) to build a plate detection system using the Python 3.0 programming language as well as the Open CV library. The information that lies in plate detection (from the way of insertion to completion and its supporting language programs) is minimal research in this field. At this stage, research can be done directly on the vehicle license plate object.